Synthetic, structural and biological studies of the ubiquitin system: chemically synthesized and native ubiquitin fold into identical three-dimensional structures. - Alexeev, D (1994)
The solid-phase chemical synthesis of ubiquitin produced a molecule with physicochemical properties similar to those of the natural protein. We have grown crystals of this synthetic ubiquitin and performed an X-ray analysis at 1.8 A resolution in order to compare the synthetic protein with the known natural structure. The crystals were isomorphous with those of the natural protein, the R-factor between them being 7.1%. Difference Fourier analysis shows that the synthetic and natural structures are indistinguishable. The co-ordinates of the natural ubiquitin (1UBQ) were used as the starting point for restrained least-squares refinement (TNT program) against the synthetic X-ray data. The refinement converged to R = 16.5% and the resulting model did not change when refined against natural ubiquitin X-ray data (R = 18.7%). From both the refinement and featureless difference Fourier synthesis, we conclude that the synthetic and natural protein structures are identical. A short discussion about the uses of proteins with 'non-standard' amino acid residues is included.